The effect of transformational leadership on decision-making participation: Moderating roles of cognitive styles / Rusli Ahmad ... [et al.] - Ahmad, Rusly; Joari, Aisyah; Abdullah Bandar, Nur Fatihah; Abdullah, Siti Mariam; Yadav, Prashanth Talwar; Daud, Dzulkiflee (Universiti Teknologi MARA Cawangan Sarawak, 2020)
This study aims to examine the effect of transformational leadership style on decision-making participation and assess the moderating role of analytical and intuitive cognitive styles. Positivistic research philosophy and quantitative methodology utilising self-report questionnaires was used in collecting data from 196 teachers of six selected educational organisations in Selangor, Malaysia. A descriptive survey design was selected, where information was collected through self-report questionnaires which were administered to the subjects by the researcher. Hierarchical regression was employed to measure the relationship between transformational leadership style and decision making participation, and subsequently evaluate the role of analytical and intuitive cognitive styles as moderators within this relationship. Findings from the study indicate that there was no significant relationship between transformational leadership style and decision making participation. Findings from the study indicate that analytical cognitive style moderates the relationship between transformational leadership style and decision making participation. Transformational leadership style with intuitive cognitive style also demonstrated a positive effect on decision-making participation, according to the value of the coefficient.